Supercritical and other high-pressure solvent systems : for extraction, reaction and material processing - Hunt, Andrew J.; Attard, Thomas M. (Royal Society of Chemistry, 2018)
This book brings together recent advances in supercritical technology and other pressurised-solvent systems.
Keywords: High pressure chemistry.; Solvent extraction.; elektronické knihy; electronic books